SINGLE OBJECT AUCTIONS WITH INTERDEPENDENT VALUES - Trifunović, Dejan (Economic Annals, 2011)
This paper reviews single object auctions when bidders’ values of the object are interdependent. We will see how the auction forms could be ranked in terms of expected revenue when signals that bidders have about the value of the object are affiliated. In the discussion that follows we will deal with reserve prices and entry fees. Furthermore we will examine the conditions that have to be met for English auction with asymmetric bidders to allocate the object efficiently. Finally, common value auctions will be considered when all bidders have the same value for the object.